Conditions for Developing Sustainable Growth of Region’s Agricultural Industry - Nemchenko, Alexander Vladimirovich; Dugina, Tatiana Aleksandrovna; Likholetov, Evgeniy Aleksandrovich; Malofeev, Aleksander Viktorovich; Likholetov, Aleksander Aleksandrovich (International Journal of Economics and Financial Issues, 2016)
In the article demonstrated the need for forming sustainable growth of agricultural industry using tools for cost optimization within the business unit. Development of effectively functioning of in-house system of cost management defines the necessity of establishing target price for agricultural products, and wherefore it was approved and suggested to use extrapolation method for the conditions of Volgograd region. Further progress of cost optimization is worthwhile investigating on the basis of classification of costs as fixed and variable costs within operating procedures, at the same time it is necessary to take into account the nominal level of profitability and environment. The proposed ways for forming the reasonable cost value would contribute to forming conditions for development of sustainable growth of agricultural industry. Keywords: economic growth; costs optimization; agricultural industry; costs of production; profitability; technical operations. JEL Classifications: Q13, R11